Multiple solutions for a fractional $p$-Kirchhoff system with singular nonlinearity - Zijian Wu (Electronic Journal of Qualitative Theory of Differential Equations)
This paper examines a class of fractional p-Kirchhoff systems driven by a nonlocal integro-differential operator with singular nonlinearity. By making use of Nehari manifold techniques, the existence of two nontrivial solutions is established. Our results extend those in Xiang et al. [Nonlinearity 29(2016), 3186–3205] for the corresponding subcritical case.